Canine Hypothyroidism with Neurological Disorders - Santos de Oliveira, Joana Thaisa; Arias Wenceslau, Amauri; Barboza da Silva, Elisângela; Lima de Lavor, Mário Sérgio; Brandão Guedes, Paula Elisa; Santiago Alberto Carlos, Renata (Acta Scientiae Veterinariae, 2022)
Background: Hypothyroidism is characterized by hypofunction of the thyroid gland. It results in deficient production of thyroid hormones. Neurological disorders resulting from hypothyroidism are rare, which highlights the importance of this study. This study reports a case of hypothyroidism in a dog with neurological clinical signs, that was treated at the Universidade Estadual de Santa Cruz’s Veterinary Hospital (HV-UESC). Case: A 4-year-old male intact Dogo Argentino breed dog, weighing 64 kg, presenting obesity, anorexia, prostration, walking in circles, and chronic dermatopathy was presented at HV-UESC. Upon physical examination, the animal presented a deficit of proprioception in the 4 limbs, with preserved superficial and deep pain. No alteration was observed in the ears, that could explained the clinical signs. In terms of dermatopathy, the animal presented symmetrical alopecia in the lateral region of the thighs and tail. Blood samples were collected for a complete blood count and biochemical tests of urea, creatinine, ALT, AST and cholesterol. Imaging radiography and ultrasonography were performed, which ruled out thoracic and abdominal changes that could be related to the case. Prior to receiving the blood test results, idiopathic encephalitis was suspected and enrofloxacin and prednisone were prescribed for 7 days. During the medication period, previous exams were provided, which indicated only increased cholesterol (500 mg/dL). The animal showed no improvement with the prescribed medication. In view of the clinical signs presented by the patient and the results of the additional tests, hormonal disease was suspected, compatible with hypothyroidism. Thus, hormonal tests of total T4, free T4, and TSH were requested, leading to verification of reduced total T4 (0.3 ng/dL) and free T4 (0.15 ng/dL) levels, and confirming the dysfunction of the thyroid gland. The previous treatment was suspended and thyroid hormone replacement was initiated. After 3 days of treatment, the neurological signs regressed and the animal became more active; after 30 days, the areas of alopecia decreased. Although the patient did not receive the recommended clinical follow-up for such cases, it was possible to establish the ideal levothyroxine dosage for the dog after appropriate adjustments, which permitted thyroid hormone levels to return to normal. Discussion: This report refers to a case of hypothyroidism in a giant dog breed. The dog in the report showed clinical signs of a dermatological, metabolic, and neurological nature, which is consistent with a lack of thyroid hormone. The main signs presented by the animal were neurological, such as walking in circles and a deficit of proprioception in the four limbs. These clinical signs are rarely mentioned in the literature associated with hypothyroidism. Laboratory abnormalities are correlated with the severity and chronicity of the disease. The animal showed a decrease in total T4 and free T4, which is to be expected in a hypothyroid animal. As a result, levothyroxine replacement treatment was initiated. The dose used for the dog, which is the recommended dose in the literature, greatly increased its total T4 levels. As a result, the dose was readjusted after a new clinical evaluation. The rate of metabolism and absorption of levothyroxine varies widely and is independent of weight. The patient showed quickly improvement in neurological signs, activity level, and serum cholesterol rate. Regarding dermatological signs and body condition, there was a more gradual improvement. This corroborates what is mentioned in the literature, which indicates that improvements can take many months. Keywords: hormonal Disease, hypothyroidism, neuropathy.